(untitled) (Journal of Hama University, 2020)
Aim of the study : Evaluation of the effect of Class II malocclusion on the facial soft tissues using frontal and lateral Photographic images . Materials and methods: The study sample included 48 patients divided equally into three groups: ( Class I , Class II div 1and Class II div 2) malocclusions with an average age of (20.17) years. The Lateral Cephalometric radiographs were performed using a (Vatech ,PHT-30LFO,Korea) X-ray imaging system to define type of Skeletal malocclusion and the photographic images were performed using a (Canon EOS 600D) digital imaging camera. The linear and angular measurements were analysed by ( Micro Dicom viewer) software. One-Way ANOVA was applied to study the effect of malocclusion on the measurements of the 3 groups . Results: The results didn’t find statistically significant differences between the three groups for ( Mouth Width angle, Interlabial angle and (v G’- Pog’) distance between soft tissue pogonion and vertical line from Glabella ) . Conclusion :We found narrowing in the middle and lower face width ,decreasing in the height of chin , Euryprosopic face in Class II div 2 . Increased Nasofacial angle which indicate increasing of the facial convexity in Class II comparing with Class I malocclusion. We didn’t find statistically significant differences in ( Mouth Width angle, Interlabial angle and (v G’- Pog’) distance between soft tissue pogonion and vertical line from Glabella ) The Upper lip protrudes from Ricketts and Steiner line in Class II div 1 and Class II div 2 more than Class I malocclusion .